المحكمة الدستورية و دورها في حماية الحقوق و الحريات -  البار, عبد الحميد; تقار, ناصر (جامعة الوادي university el-oued, 2022)
إن تفعيل دور المحكمة الدستورية في مجال الرقابة الدستورية متوقف على النظام الذي يتم اعتماده للفصل في الدفع بعدم الدستورية ، بحيث يكون ضيقا ومتشددا في النظام القائم على التصفية المزدوجة كما هو معمول به في الجزائر وفرنسا، بينما يكون هذا الدور مــــــــرنا وواسعا في النظام القائم على الإحالة المباشرة كما هو الحال في إسبانيا . إن دور المحكمة الدستورية في حماية الحقوق والحريات سيتعزز أكثر إذا كان أكثر تجانسا على نحو يساهم به في إنجاح مسعى المؤسس الدستوري، كما أن انخراط أسرة الدفاع في هذا المسعى باعتبار أن مهنتهم الأساسية في الدفاع عن حقوق الإنسان و حرياته سيشكل مساهمة كبيرة في تطهير المنظومة القانونية من الأحكام التشريعية التي تنتهـــــــــك الحقوق والحريات المكرسة دستوريا. The activation of the role of the Constitutional Court in the field of constitutional oversight depends on the system that is adopted to adjudicate the defense of unconstitutionality, so that it is narrow and strict in the system based on double liquidation as is the case in Algeria and France, while this role is flexible and broad in the system based on referral Direct as in Spain. The role of the Constitutional Court in protecting rights and freedoms will be more enhanced if it is more homogeneous in a way that contributes to the success of the endeavor of the constitutional founder, and the involvement of the defense family in this endeavour, given that their primary profession in defending human rights and freedoms will constitute a significant contribution to purifying the legal system Among the legislative provisions that violate the constitutionally enshrined rights and freedoms.
مذكرة ماستر